Impacto de métodos de cocção no teor de colesterol e 7-cetocolesterol e na composição de filés de merluza (Merluccius hubbsi) e de pescada-branca (Cynoscion leiarchus) - Maria Tereza de Freitas (2014)
The present study aimed to evaluate the influence of different cooking methods on the proximate composition and cholesterol oxidation in fish. The cooking methods and fish species were selected based on the increased use in Brazilian food service. Thus the proximate composition, cholesterol and 7-ketocholesterol were measured in raw Atlantic hake (Merluccius hubbsi) and smooth weakfish (Cynoscion leiarchus) fillets and in fillets subjected to the following cooking methods: baking in an electric or microwave oven; baking, grilling or stewing in a steam-convection oven; simmering on a stove; electric grilling; and deep frying. The cooking affected significantly (p < 0.05) the moisture, lipid, ash and energy values in all of the samples for both species. It was not possible appoint to a single method of cooking as the best, however, considering the highest lipid content, highest energy value and lowest protein content by fried fillets, this would be the least recommended method. Regarding the content of cholesterol, the fillets thermally processed from both species exhibited significantly (p < 0.05) lower levels than the raw samples with maximum reduction of 64.90% for Atlantic hake and 65.08% in the fillets of smooth weakfish. In the cooked samples 7-ketocholesterol, used as an indicator of oxidation, was detected at levels significantly different (p < 0.05) with the highest levels for the treatments in which high temperatures and long cooking times were used. The highest levels of 7-ketocholesterol were for fillets of Atlantic hake submitted to GCO (13.94 g.g-1), BEO (13.41 g.g-1) and BCO treatments (12.00 g.g- 1). The lowest level of 7-ketocholesterol was detected in the treatment SCO (6.90 g.g-1 hake fillet and 6.47 g.g-1 for hake fillets).The lowest level of 7-ketocholesterol was detected in fillets cooked by stewing and the highest level was found in fillets processed using electric or combination ovens, in which high temperatures and long cooking times were used. These results indicate the necessity of revising the baking procedures for fish to increase the healthiness of food.